2013
DOI: 10.1089/jpm.2012.0413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Participation among Ethnic/Racial Minority and Majority Patients with Advanced Cancer: What Factors Most Influence Enrollment?

Abstract: Patient race/ethnicity was not associated with clinical trial enrollment after adjustment for socioeconomic covariates. Patients with advanced cancer endorsing less engagement in end-of-life planning were more likely to be enrolled in a clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
4
16
2
Order By: Relevance
“…Another important point is that older patients are more likely to decline participation (Ellis, Butow, Tattersall, Dunn, & Houssami, ; Go et al., ). Patients with poor health status also decline participation in clinical trials more often (Jimenez et al., ; Mao et al., ). Results concerning sex disparities in trial participation are inconclusive so far.…”
Section: Introductionmentioning
confidence: 99%
“…Another important point is that older patients are more likely to decline participation (Ellis, Butow, Tattersall, Dunn, & Houssami, ; Go et al., ). Patients with poor health status also decline participation in clinical trials more often (Jimenez et al., ; Mao et al., ). Results concerning sex disparities in trial participation are inconclusive so far.…”
Section: Introductionmentioning
confidence: 99%
“…Low socioeconomic status and rural residence also appear to be associated with low enrollment in clinical trials. Although racial/ethnic inequalities in cancer clinical trial participation have been extensively reported in adults [8,[12][13][14][15][16][17][18][19], little work has been done to describe and understand racial/ethnic disparities in research protocol enrollment Background. Survival rates in pediatric oncology have improved dramatically, in part due to high patient participation in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic affected the communication about the trial and made the patients unable to fully understand the trial information provided (Thorne, Taylor, Stephens, Kim-Sing, & Hislop, 2013). Research has also suggested that patients with advanced cancer who did not have, or did not wish to have, an end-of-life discussion, were more likely to be enrolled in trials (Jimenez et al, 2013). Another study found that experience had an influence on the decision because patients with prior trial experience were more prone to participate again (Lee et al, 2012).…”
Section: Discussion Of Findingsmentioning
confidence: 99%